Appendiceal Orifice Inflammation in Ulcerative Colitis Mimicking Mucosa-Associated Lymphoid Tissue Lymphoma in the Cecum. (7th October 2020) - Iwamuro, Masaya; Takahashi, Takahide; Tanaka, Takehiro; Toji, Tomohiro; Hiraoka, Sakiko; Kawano, Seiji; Kawahara, Yoshiro; Okada, Hiroyuki
Abstract : A 55-year-old Japanese woman, who had been diagnosed with ulcerative colitis at 18 years of age, underwent screening endoscopy examinations. Esophagogastroduodenoscopy revealed an extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) of the stomach. Colonoscopy showed a slightly elevated reddish lesion with dilated microvessels but no erosions or ulcers. Although MALT lymphoma in the cecum was endoscopically suspected, flow cytometry and pathological analyses led to the diagnosis of appendiceal orifice inflammation in ulcerative colitis. This case highlights the diversity of the endoscopic appearance of appendiceal orifice inflammation in ulcerative colitis.